Enhanced sensitivity of humidity sensor prepared using vertically aligned V-doped TiO2 Nanorods Array / Mohamed Zahidi Musa ... [et al.] - Musa, Mohamed Zahidi; Mamat, Mohamad Hafiz; Othman, M.A; Shameem, Banu (I. B.); Nagamalai, Vasimalai; Malek, Mohd Firdaus; Rusop, Mohamad (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
This article reports on the performance of vanadium-doped TiO2 nanorod arrays (TNA)-based humidity sensor. The sensing material was prepared using a facile solution immersion method. Humidity sensor was fabricated using the prepared thin films and was tested using humidity chamber and a current measuring circuit, built with microcontroller. Improvement to the sensitivity was observed for the V-doped TNA sensor with sensitivity value of 15.0 compared to 9.9 for the undoped TNA sensor. The increased performance is attributed to the enlargement of nanorods diameter, improvement of crystallinity and the increase in oxygen vacancy defect sites of the V-doped sample.